Orthotropic material properties of the gerbil basilar membrane. - Liu, Shuangqin.; White, Robert D. (Tufts University. Tisch Library., 2018)
In this paper, two sets of experimental results to extract the two effective elastic moduli, the effective shear modulus, and the effective Poisson's ratio for the gerbil cochlear partition are analyzed. In order to accomplish this, a geometrically nonlinear composite orthotropic plate model is employed. The model is used to predict both out-of-plane and in-plane motion of the partition under a static finite area distributed load. This loading condition models the small, but finite size, probe tips used in experiments. Both in-plane and out-of-plane motion are needed for comparison with recent experimental results. It is shown that the spatial decay rate (the space constant) for the in-plane deflection is different than for the out-of-plane deflection, which has a significant effect on the derived partition properties. The size of the probe tip is shown to have little influence on the results. Results are presented for two types of boundary conditions. Orthotropy ratios determined from the experimental data are found to vary with longitudinal position and choice of boundary conditions. Orthotropy ratios (the ratio of the two elastic moduli) are in the range of 65 close to the base to 10 in the upper middle turn of the cochlea. Copyright 2008 Acoustical Society of America. This article may be downloaded for personal use only. Any other use requires prior permission of the author and the Acoustical Society of America.